Species Distribution Models of the Spartina alterniflora Loisel in Its Origin and Invasive Country Reveal an Ecological Niche Shift - Yuan, Yingdan; Tang, Xinggang; Liu, Mingyue; Liu, Xiaofei; Tao, Jun (Frontiers in Plant Science, 2021)
Spartina alterniflora is a perennial herb that is native to the American Atlantic coast and is the dominant plant in coastal intertidal wetlands. Since it was introduced to China in 1979 and spread rapidly along the coastal, causing multiple hazards. To control the further spread of S. alterniflora in China, we first reconstructed the history of the spread of S. alterniflora in the invasion and origin country, and found that S. alterniflora spreads from the middle coast to both sides of the coast in China, while it spreads from the west coast to the east coast in America. Furthermore, by comparing 19 environmental variables of S. alterniflora in the invasion and origin country, it was found that S. alterniflora is more and more adaptable to the high temperature and dry environment in the invasion country. Finally, we predicted the suitable areas for this species in China and America using the MaxEnt model and ArcGIS. Overall, through analysis on the dynamic and trend of environmental characteristics during the invasion of S. alterniflora, and then predicting its suitable area in the invasion area, it provides guidance for preventing its reintroduction and preventing its further spread. It has reference significance for studying other similar alien plants, and has important enlightening significance for its invasion and spread in similar areas.